DESEMPENHO DE ESCOLAS PÚBLICAS DE ESPERA FELIZ/MG NAS AVALIAÇÕES DO PROEB/SIMAVE – 2011 A 2016 - Mendes Mateus, Larissa; da Silva Oliveira, Luciane (LINKSCIENCEPLACE, 2026)
SIMAVE evaluations are carried out to measure students' performance in Mathematics and Portuguese Language and to monitor the improvement of the quality of education offered in the public network of Minas Gerais. The research had as objective to analyze the performance in Mathematics of two public schools of Espera Feliz / MG, in the period from 2011 to 2016, and to verify the perception of Mathematics teachers of these schools regarding the external evaluation processes and the influence of the same in their everyday practice. The data were collected on the SIMAVE website and through interviews with the teachers of these schools. It was observed that all the high school classes of the two schools presented poor performance and that 62.5% of the teachers do not know the results of the school where they work. Knowing and analyzing the results of these evaluations can contribute to fostering public policy for improving the quality of education.